Common Bean Subtelomeres Are Hot Spots of Recombination and Favor Resistance Gene Evolution - Chen, Nicolas W. G.; Thareau, Vincent; Ribeiro, Tiago; Magdelenat, Ghislaine; Ashfield, Tom; Innes, Roger W.; Pedrosa-Harand, Andrea; Geffroy, Valérie (Frontiers in Plant Science, 2018)
Subtelomeres of most eukaryotes contain fast-evolving genes usually involved in adaptive processes. In common bean (Phaseolus vulgaris), the Co-2 anthracnose resistance (R) locus corresponds to a cluster of nucleotide-binding-site leucine-rich-repeat (NL) encoding sequences, the prevalent class of plant R genes. To study the recent evolution of this R gene cluster, we used a combination of sequence, genetic and cytogenetic comparative analyses between common bean genotypes from two distinct gene pools (Andean and Mesoamerican) that diverged 0.165 million years ago. Co-2 is a large subtelomeric cluster on chromosome 11 comprising from 32 (Mesoamerican) to 52 (Andean) NL sequences embedded within khipu satellite repeats. Since the recent split between Andean and Mesoamerican gene pools, the Co-2 cluster has experienced numerous gene-pool specific NL losses, leading to distinct NL repertoires. The high proportion of solo-LTR retrotransposons indicates that the Co-2 cluster is located in a hot spot of unequal intra-strand homologous recombination. Furthermore, we observe large segmental duplications involving both Non-Homologous End Joining and Homologous Recombination double-strand break repair pathways. Finally, the identification of a Mesoamerican-specific subtelomeric sequence reveals frequent interchromosomal recombinations between common bean subtelomeres. Altogether, our results highlight that common bean subtelomeres are hot spots of recombination and favor the rapid evolution of R genes. We propose that chromosome ends could act as R gene incubators in many plant genomes.